In vivo evaluation of clinical performance of Cention N and glass ionomer cement in proximal restorations of primary molars - Divya Arora; Mansi Jain; H P Suma Sogi; Prinka Shahi; Ishita Gupta; Meera Sandhu (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2022)
Introduction: Restoring a proximal lesion in primary tooth has met with many challenges which has led to evolution of many materials. An alternative to Glass Ionomer Cements which has fluoride releasing capacity, offers good bond strength and is esthetic have been long looked for. Aim: This study aimed to compare the clinical performance of GIC and Cention N in proximal restorations of primary molars. Materials and Methodology: A prospective study was conducted on 154 primary molars in patients aged between 5 and 8 years using a split-mouth design. Patients were divided into two groups. Control group restored with GIC and study group received Cention N. Both groups were assessed at baseline 3, 6 and 9 months according to Ryge criteria and data was statistically analysed using Fisher's Exact. Results: Statistically significant difference was found between GIC and Cention N restorations for color match at baseline and color stability at 3 months (P < 0.001), while the other parameters did not show any significant difference among the two restorative materials. Conclusion: Cention N can be used as a suitable alternative to GIC for restoring Class II restorations in primary molars.